Cost-effectiveness of 4 mg dibotermin alfa/absorbable collagen sponge versus iliac crest bone graft for lumbar degenerative disc disease in the United Kingdom. (31st December 2022) - Cumming, David; Song, Fujian; Taylor, Rod S.; Zahra, Mehdi; Williams, Adrian; Eggington, Simon
Abstract: Aims: To develop a model to evaluate the cost-effectiveness of 4 mg dibotermin alfa/absorbable collagen sponge (ACS) versus iliac crest bone graft (ICBG) in patients with lumbar degenerative disc disease in the United Kingdom. Materials & methods: A Markov decision-analytic model was constructed to calculate costs and quality-adjusted life-years over a 4-year time horizon in each treatment group, from a United Kingdom National Health Service perspective. An individual patient data meta-analysis was undertaken to synthesize data from four randomized controlled trials and two single-arm studies concerning health-related quality of life and procedural resource use. Current cost data from the United Kingdom were then applied to determine the overall mean cost per patient in each group. One-way and probabilistic sensitivity analyses were undertaken to explore the impact of parameter uncertainty. Results: The model predicted 4-year discounted cost savings of £192 per patient treated with dibotermin alfa/ACS, compared with ICBG, and a gain of 0.0114 QALYs per patient over the same time period. Sensitivity analyses indicated that the results were most sensitive to variability in the differences in health-related quality of life and secondary surgery rate, with dibotermin alfa/ACS having a 60% probability of being cost-effective at a willingness-to-pay threshold of £20, 000 per QALY gained. Limitations: There is uncertainty in the difference in cost and QALYs between the two groups. However, comprehensive sensitivity analyses were undertaken to explore this and present the results in a transparent manner. Conclusions: Our results provide an economic case for the use of 4 mg dibotermin alfa/ACS versus iliac crest bone graft, with additional health benefits predicted at reduced overall cost.